Modified lung ultrasound score for improved monitoring of pARDS on ECMO, a case report - E. Küng; L. Aichhorn; M. Di Nardo; F. Cardona; A. Berger; R.I. Milos; M. Watzenböck; J.B. Brandt (BMC Pediatrics)
Abstract Background Lung ultrasound scoring is a validated tool for assessing lung pathology. However, existing scoring systems typically overlook the size of consolidations, limiting their accuracy in certain clinical scenarios. Case presentation We describe the first application of adding the maximum consolidation depth in centimeters (cm) to the conventional score. This modification (LUS+) was used in an eight-month-old patient with severe respiratory failure undergoing extracorporeal life support (ECLS). Spearman’s correlation analysis revealed a similar correlation in LUS+ compared to conventional lung ultrasound score. Importantly, LUS + showed improvement following cessation of lung rest on day 5, preceding the changes observed in conventional lung ultrasound scores and tidal volume measurements on day 9. Conclusions The integration of consolidation depth, quantified in centimeters, represents a valuable refinement of the conventional lung ultrasound score, enhancing its utility in monitoring pediatric acute respiratory distress patients undergoing ECLS.